ANALISIS RETROSPEKTIF PENERAPAN LATIHAN INTERVAL TERHADAP KAPASITAS POWER ENDURANCE PEMAIN FUTSAL PUTRI UPI - Risty Dewi Utami; Dikdik Zafar Sidik; Dede Rohmat Nurjaya; Fitri Rosdiana (Universitas Hamzanwadi, 2026)
The problem addressed in this study is the continued decline in the physical performance of female futsal players when performing repetitive explosive movements during matches, which highlights the need for appropriate training methods to improve power endurance. This study aims to retrospectively analyze the application of Short Interval Training based on Maximum Aerobic Speed (MAS) on the power endurance capacity of female futsal players at the Indonesia University of Education (UPI), as well as to examine the relationship between aerobic endurance capacity and power endurance. The method used was a quantitative descriptive approach with a retrospective ex post facto design. A sample of 5 athletes was selected via purposive sampling from a population of 40 athletes. Data were obtained from documentation of the Balke Test and 1-Minute Hurdle Jump Test results before and after the training program, which consisted of 16 sessions. Analysis results showed that the average Hurdle Jump count changed from 79.2 repetitions (pre-test) to 78.0 repetitions (post-test), with an average of 78.6 repetitions. Spearman’s correlation test indicated a moderate positive relationship (r = 0.600), but it was not statistically significant (p = 0.285). In conclusion, aerobic endurance capacity has not been shown to have a significant relationship with power endurance in this sample; therefore, the development of power endurance should be pursued through a training program that combines aerobic, anaerobic, strength, and explosive power training.